GCKIII (Germinal Center Kinase III) Kinases STK24 and STK25 (Serine/Threonine Kinase 24 and 25) Inhibit Cavernoma Development. Issue 3 (March 2022) - Sartages, Miriam; García-Colomer, Mar; Iglesias, Cristina; Howell, Brian W.; Macía, Manuel; Peña, Patricia; Pombo, Celia M.; Zalvide, Juan
Abstract : Background: Cavernous cerebral malformations can arise because of mutations in the CCM1, CCM2, or CCM3 genes, and lack of Cdc42 has also been reported to induce these malformations in mice. However, the role of the CCM3 (cerebral cavernous malformation 3)-associated kinases in cavernoma development is not known, and we, therefore, have investigated their role in the process. Methods: We used a combination of an in vivo approach, using mice genetically modified to be deficient in the CCM3-associated kinases STK24 and STK25 (serine/threonine kinases 24 and 25), and the in vitro model of human endothelial cells in which expression of STK24 and STK25 was inhibited by RNA interference. Results: Mice deficient for both Stk24 and Stk25, but not for either of them individually, developed aggressive vascular lesions with the characteristics of cavernomas at an early age. Stk25 deficiency also gave rise to vascular anomalies in the context of Stk24 heterozygosity. Human endothelial cells deficient for both kinases phenocopied several of the consequences of CCM3 loss, and single STK25 deficiency also induced KLF2 expression, Golgi dispersion, altered distribution of β-catenin, and appearance of stress fibers. Conclusions: The CCM3-associated kinases STK24 and STK25 play a major role in the inhibition of cavernoma development. Abstract : Supplemental Digital Content is available in the text.